Characterizing pediatric discharge diagnoses associated with daily extreme heat exposure in the Midwestern US: A retrospective case-crossover study - Sarah Oerther; Zachary Phillips; Zidong Zhang; Joanne Salas; Sarah Farabi; Tamara Otey (Heliyon)
Aim: To explore the association between daily extreme heat exposure (daily mean temperature is greater than the 90th percentile for the month) and pediatric (birth to 18 years old) urgent care clinic, emergency department, and inpatient hospitalization discharge diagnoses for any causes and 12 individual morbidities of interest. Design: A time-stratified, case-crossover study design. Methods: We analyzed discharge diagnoses from the Saint Louis University-Sisters of St. Mary, a non-profit healthcare system in the United States, using the Virtual Data Warehouse. Our analysis encompassed urgent care clinic visits, emergency department visits, and hospitalizations within a Midwestern healthcare network across Missouri, Wisconsin, the Oklahoma City metropolitan area, and Southern Illinois, in the United States. Our study focused on all causes and examined 12 specific morbidities of interest. We focused on pediatric patients during the warm season months of May through September in 2017–2022. For all outcome models, an overall model was calculated and then each model was stratified by age, sex, race, and neighborhood socioeconomic status, excluding strata with unknown values. Results: We found significant associations with dehydration, general symptoms, heat-related illnesses, and infections. The impact of extreme heat exposure varied across demographics, with vulnerable groups including children aged one to four, males, and individuals from low socioeconomic status areas. Conclusions: Our findings highlight important opportunities for health promotion in communities and preschools. Better informing caregivers of the risks and implementing policy level initiatives may help reduce pediatric exposure to extreme heat. Future research should focus on longitudinal studies to explore these dynamics further and develop effective heat mitigation strategies to protect vulnerable pediatric populations from the adverse effects of extreme heat.